Description of facies of the Suretka Formation near Siquirres and his relation with depositional environments - Vargas, Asdrúbal (2017)
In this work is presented a description of sedimentary facies identified for the Suretka Formation near the town of Siquirres, Limón. The description was carry out with the inspections of underground excavations, outcrops in creeks, shafts, and boreholes during the construction stage of the Reventazón Hydroelectric power plant. It was identified three sedimentary facies: conglomerate facies, sandstone lenses with fine to very fine conglomerate and tuff lenses facies. The conglomerate facies is characterized by igneous blocks sumerged in a loam sandy matrix. In general can be found in this facies metric to decametric bedding with bad gradation. By the other side facies of sandstone lenses and fine conglomerates are described as strata of the centimeter order with presence of both parallel and cross laminations in sandstone lenses and reverse and normal gradations in fine conglomerate lenses. The facies analysis allows the identification of an environment of subareal deposition associated with alluvial fans. For the facies of conglomerates, a proximal alluvial fan environment is established and for the facies of lenses of sandstones and intercalations of fine to very fine conglomerates a environment of medium alluvial fan with meandering sedimentary processes like longitudinal or point bars.